In vivo and clinical application of strontium-enriched biomaterials for bone regeneration: A systematic review. Issue 6 (June 2017) - Neves, N.; Linhares, D.; Costa, G.; Ribeiro, C. C.; Barbosa, M. A.
Abstract : Objectives: This systematic review aimed to assess the in vivo and clinical effect of strontium (Sr)-enriched biomaterials in bone formation and/or remodelling. Methods: A systematic search was performed in Pubmed, followed by a two-step selection process. We included in vivo original studies on Sr-containing biomaterials used for bone support or regeneration, comparing at least two groups that only differ in Sr addition in the experimental group. Results: A total of 572 references were retrieved and 27 were included. Animal models were used in 26 articles, and one article described a human study. Osteoporotic models were included in 11 papers. All articles showed similar or increased effect of Sr in bone formation and/or regeneration, in both healthy and osteoporotic models. No study found a decreased effect. Adverse effects were assessed in 17 articles, 13 on local and four on systemic adverse effects. From these, only one reported a systemic impact from Sr addition. Data on gene and/or protein expression were available from seven studies. Conclusions: This review showed the safety and effectiveness of Sr-enriched biomaterials for stimulating bone formation and remodelling in animal models. The effect seems to increase over time and is impacted by the concentration used. However, included studies present a wide range of study methods. Future work should focus on consistent models and guidelines when developing a future clinical application of this element. Cite this article: N. Neves, D. Linhares, G. Costa, C. C. Ribeiro, M. A. Barbosa. In vivo and clinical application of strontium-enriched biomaterials for bone regeneration: A systematic review. Bone Joint Res 2017;6:366–375. DOI: 10.1302/2046-3758.66.BJR-2016-0311.R1.